Factors associated with low back overuse injuries in sports science students – a prospective study - Mikša, Maja (Zdravstveno varstvo, 2025)
Background: Sports science students (SPS) are more likely to be affected by low back pain (LBP) compared to the young, physically active population. The aim of this prospective study was to evaluate potential risk factors for LBP in the population of SPS. Methods: Before the beginning of the study the participants (n=54) performed initial physical performance testing and gave blood samples. Then they were followed up for 10 weeks. The observed outcome was LBP occurrence. The presence of the observed outcome was recorded using the Oslo Sports Trauma Research Centre Overuse Injury Questionnaire weekly. The association between LBP and potential explanatory factors - potential overtraining parameters (e.g. ferritin and iron levels, amount of sleep) and motor ability parameters (e.g. muscle strength, vertical jump) - was assessed using multiple binary logistic regression. Results: During the 10 week prospective follow-up LBP was the most common problem affecting 13% of students. From the group of explanatory factors for LBP only two were included in the final model as statistically significant: low ferritin level (OR=8.70, p=0.008), and history of previous LBP (OR=8.69; p=0.006) made students more likely experience new LBP problems. Conclusions: The SPS that are more at risk of experiencing LBP are those with a history of LBP and those with low ferritin level. Awareness should be raised among students about the importance of comprehensive LBP prevention (preventive exercise, preventive medical check up including blood test).
Keywords: bolečine v križu; ferritin level; low back pain; mišična moč; muscle strengt; prevention; preventiva; raven feritina; students; študenti